Sapphirina iris Dana, 1849 and S. sinuicauda Brady, 1883 (Copepoda, Cyclopoida): Predators Of salps in Monterey Bay and the Gulf Of California. - Gasca, R., E. Suárez-Morales & S.H.D. Haddock (Crustaceana, 2015)
Species of the copepod genus Sapphirina Thompson, 1829 are deemed as specialized predators of salps. There are only a few documented records of such copepods actually found within their prey. During two cruises of the R/V “Western Flyer” of MBARI (Monterey Bay Aquarium Research Institute), SCUBA diving was used to sample the zooplankton in Monterey Bay and the Gulf of California. An ovigerous female of Sapphirina iris Dana, 1849 and a male of S. sinuicauda Brady, 1883 were collected inside aggregate zooids of the salp Pegea confoederata (Forskål, 1775). Also, two adult females of S. iris were recorded inside P. socia (Bosc, 1802); both were lodged near the oriﬁces they made to enter the salp’s body. This is the ﬁrst documented record of the association involving these sapphirinid copepods lodged in their prey. The high number of eggs of the female S. iris supports the suggestion that sapphirinids have a higher fecundity than that of other planktonic copepods, an adaptive strategy related to their mode of life. The ﬁnd of the male S. sinuicauda attached inside the salp differs from earlier observations on the behaviour of sapphirinid males. Key words. — copepods, zooplankton, predator-prey association, sapphirinids, salps